Arbutin protects against methotrexate-induced pulmonary injury in rats via modulation of oxidative stress, inflammation, and ER stress - Turkmen Alemdar, Nihal; Demir, Selim; Yulug, Esin; Erdogan, Nadire Sevdenur; Ayazoglu Demir, Elif; Mentese, Ahmet; Aliyazicioglu, Yuksel (Frontiers in Veterinary Science, 2025)
IntroductionMethotrexate (MTX) is a widely utilized agent in the treatment of cancer, yet it is notable that it can induce pulmonary toxicity in cases of high-dose chemotherapy. Arbutin (ARB) is a hydroquinone compound that is present in members of the Lamiaceae, Ericaceae and Rosaceae families, and experimental studies have demonstrated its capacity for lung protection. The present study aimed to determine whether ARB could reduce the pulmonary toxicity of MTX and to explore the underlying mechanisms.MethodsThe lung toxicity rat model was created by means of a single intraperitoneal injection of MTX at a dose of 20 mg/kg. The animals were then treated with two different doses of ARB (50 and 100 mg/kg) for a period of 7 days. Following the conclusion of the treatment period, a histopathological examination of the lung tissue samples was conducted. The remaining tissue samples were evaluated for oxidative stress (OS), inflammation, endoplasmic reticulum stress (ERS), sirtuin 1 (SIRT1)/nuclear factor erythroid-related factor 2 (Nrf2) pathway, and apoptosis for further analysis.ResultsThe administration of MTX resulted in the inhibition of SIRT1/Nrf2 in lung tissue, accompanied by an escalation in OS, inflammation, ERS, and apoptosis levels. This was concomitant with a significant enhancement in the severity of histopathological findings. Nevertheless, ARB reversed MTX-induced biochemical and pathological changes through SIRT1/Nrf2 modulation.DiscussionIt is asserted that further comprehensive studies are required to support the hypothesis that ARB has the potential to improve oxidative and inflammatory lung injury via SIRT1/Nrf2 modulation.